Exclusivity in the collection of material for oncotic colpocytology examination: nurses' perception - Letícia Lima de Oliveira; Marllon Rodrigo Sousa Santos; Ivaneide Leal Ataíde Rodrigues; Suzana Rosa André; Ingrid Fabiane Santos da Silva; Laura Maria Vidal Nogueira (Universidade Federal de Santa Maria, 2020)
Aim: To analyze nurses' perceptions about the exclusivity of material collection for oncotic colpocytology. Method: a descriptive study of qualitative nature, having as participants 18 nurses from Municipal Health Units of Belém-Pará. Data collection took place between June and August 2017 with the aid of a semi-structured interview script, and content analysis was used to interpret the results. Results: the data correspond to perceptions about the collection of the oncotic colpocytology exam, subdivided into perceptions about the collection performed by the nurse and nursing technician, facilities and difficulties in collecting and changes in the routine of nurses. Conclusion: the perceptions are heterogeneous, but converge in recognizing the need for nurses to add technical and scientific knowledge to perform the collection of material for oncotic colpocytology, due to the high complexity of the technique.